2017
DOI: 10.1002/ceat.201600364
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Homogenization: Simplified Drop Deformation Estimate during Transition through Orifices

Abstract: The breakup process of primary drops during transition through slots or small openings has been examined frequently in the past. Recent experiments show strong influence of the dispersed-phase viscosity on the deformation of drops at the inlet of orifices that cannot be explained by the equilibrium approach based on capillary numbers or viscosity ratios only. It is necessary to account for the strongly transient character of the process. A quantitative treatment of this behavior based on relationships from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This mismatch may cause differences when investigating the droplet deformation and breakup in detail at the 50-fold scale. Since it is assumed that the diffusion of the emulsifier in the original scale process is much slower than the breakup process [6,29,30], the influence of the emulsifier on the breakup is, however, expected to be moderate, which would still allow the comparison of the droplet breakup in all three scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mismatch may cause differences when investigating the droplet deformation and breakup in detail at the 50-fold scale. Since it is assumed that the diffusion of the emulsifier in the original scale process is much slower than the breakup process [6,29,30], the influence of the emulsifier on the breakup is, however, expected to be moderate, which would still allow the comparison of the droplet breakup in all three scales.…”
Section: Discussionmentioning
confidence: 99%
“…Any results from this scaled experimental setup therefore need to be interpreted with caution. It is presumed, though, that the diffusion time of the emulsion to the newly created surface during droplet deformation is much higher than the breakup process itself [29,30]. Hence, the influence of the higher interfacial tension on the droplet may be moderate.…”
Section: Matching Of Orifice Dimensions and Materials Systemmentioning
confidence: 99%
“…The correlation was only proven for small constant stresses under laminar flow conditions. Simulations of Walzel [ 10 ] showed that this correlation may also be applicable to the droplet deformation behaviour during high‐pressure homogenization. The influence of the interfacial tension on the droplet deformation should increase with decreasing viscosity ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Droplet deformation in an optically accessible step-type orifice was evaluated by Kelemen et al [9] They found that the droplets are supercritically Ca > Ca crit ð Þdeformed in the inlet and only break up downstream of the orifice exit. Walzel [10] simulated the droplet deformation inside a passage through an orifice on the centreline using an approach stated by Cox [6] and Kalb et al [11] These findings were later validated using experimental data from a scaled orifice setup whereby a good agreement was found between the simulation and the experiment at limited settings. [12] Among others, Feigl et al [13] and Hövekamp [14] used computational fluid dynamics (CFD) simulations to determine the stress history on the droplet streamline with changing stress loads and constant interfacial tension, which was subsequently correlated with the droplet deformation from simulations and experimental data.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation